Development of a 2d microfluidic paper-based analytical device for diagnosis of canine visceral leishmaniasis - Carvalho, Hianka Jasmyne Costa de (2024)
Visceral leishmaniasis (VL) is a neglected tropical disease caused by the protozoan Leishmania infantum and affecting humans and dogs in urban areas. The diagnosis of canine visceral leishmaniasis (CVL) is a tool for the prevention and prophylaxis of VL, since the presence of infected dogs influences the disease in humans as well. In this way, clinical signs are associated with results from rapid and confirmatory tests, which may present varying sensitivity and specificity, and cross-reaction with other pathogens, in addition to the high cost associated with sample collection, specialized labor, storage and laboratory infrastructure. In the present study, we developed a 2D paper-based microfluidic device for the diagnosis of CVL through the detection of the canine IgG anti- L. infantum in an indirect immunoassay. Instead of using non-stable enzymes for signal transduction, we coupled highly stable ionic probes to the detection antibody, increasing the stability and robustness of our device when compared to conventional colorimetry- based assays. The immunoassay is analyzed by paper spray mass spectrometry (MS), detecting the presence of ionic probes. The detection and quantification limits here obtained indicate a high sensitivity of our device, and the clinical study carried out highlights its ability to differentiate LVC positive samples from negative samples. Finally, the stability studies carried out demonstrated that the device will serve for stable remote sampling and storage at room temperature. By decoupling the sample collection and analysis steps, associating portable mass spectrometers for the device analysis, we intend in the future to make the CVL diagnosis easy, accurate, and widely accessible, combining the ease of rapid methods with the precision of gold standard methods of CVL diagnosis.